Some new data concerning the mutagenic action of DNA - Gershenson, S.M.; Alexandrov, Yu.N. (Биополимеры и клетка, 1994)
It is shown that spermatozoa of Drosophila melanogaster can transfer molecules of exogenous DNA (or their fragments) from a solution of this DNA injected into the haemocel of an adult male into the ooplasm of the egg. As a result, mutations induced in the descendants arise both in the paternal and the maternal chromosomes obtained by them. The mutagenic effect of exogenous DNA has a prolonged character inducing mutations in the descendants during many cell generations after DNA-treatment of their father. The mechanism of such a prolongation of the mutagenic action of DNA is discussed. Выявлено, що сперматозоїди самця Drosophila melanogaster здатні переносити до ооплазми запліднюючого яйця молекули екзогенної ДНК (або їxнi фрагменти) з розчину цієї ДНК, що введений до гемоцелі самця; внаслідок цього індуковані ДНК мутації виникають у нащадків у хромосомах, одержаних як від батька, так i від матеpi. Показано, що мутагенна дія екзогенної ДНК має пролонгований характер i індукує у нащадків мутації протягом ряду клітинни поколінь. Обговорюється вірогідний механізм такої пролонгованої дії. Выявлено, что сперматозоиды самца Drosophila melanogaster способны переносить в ооплазмы оплодотворяющего яйца молекулы экзогенной ДНК (или иx фрагменты) из раствора другой ДНК, введен в гемоцели самца; вследствие этого индуцированные ДНК мутации возникают у потомков в хромосомах, полученных как от отца, так и от матеpи. Показано, что мутагенное действие экзогенной ДНК имеет пролонгированный характер и индуцирует у потомков мутации течение ряда клеточных поколений. обсуждается возможный механизм такой пролонгированного действия.